Exploration of susceptibility genes in type 2 diabetes mellitus among Chinese Hui and Han people - Kang, Jianhua; Shen, Xingya; Feng, Shaohua; Li, Delai; Yuan, Haisheng; Li, Na; Wei, Hexi; Yang, Lishun (Journal of the Pakistan Medical Association, 2025)
Objectives: To identify the differentially expressed genes among Chinese Hui and Han individuals to identify potential susceptibility genes for type 2 diabetes mellitus. Method: The case-control study was conducted at Tianjin Beichen District Chinese Medicine Hospital, China, from January to September 2021, and comprised Hui patients with diabetes in group A1 and Han patients with diabetes in group B1. Hui healthy, non-diabetic patients were enrolled in group C1, and healthy, non-diabetic Han patients were enrolled in group D1. Gene expression in whole blood samples was analysed using microarray technology. Data was analysed to identify differentially expressed genes, followed by Gene Ontology terms and Kyoto Encyclopaedia of Genes and Genomes pathway-enrichment analyses. Additionally, a Protein-Protein Interaction network analysis was performed based on the identified differentially expressed genes. Finally, quantitative reverse transcription-polymerase chain reaction was employed to validate the selected susceptibility genes. Results: Of the 51 subjects, 11(21.7%) were in group A1, 14(27.4%) in group B1, 14(27.4%) in group C1, and 12(23.5%) in group D1. On comparison of A1 vs. B1, A1 vs. C1, B1 vs. D1, and C1 vs. D1, 953, 289, 598 and 382 differentially expressed genes were identified, respectively. Additionally, 57, 52, 55 and 54 Gene Ontology terms, as well as 192, 103, 143 and 112 Kyoto Encyclopaedia of Genes and Genomes pathways were identified for the overlapping differentially expressed genes that were present in at least one pair of the 4 sets. The quantitative reverse transcription-polymerase chain reaction results for susceptibility genes were consistent with the findings of bioinformatics analysis. Conclusion: Insulin-like Growth Factor 1 Receptor, chondrodysplasia punctata-diacylglycerol synthase 1, Laminin Subunit Alpha 4, Sialic Acid-Binding Immunoglobulin-like Lectin 14, Chromosome 18 Open Reading Frame 61 and Ribosomal Protein S26 were identified as susceptibility genes for type 2 diabetes mellitus in different study populations. Key Words: Diabetes mellitus, Type 2, Differentially expressed genes, Ethnic groups, Microarray analysis, Disease susceptibility.